Information for contributors and readers for issue 4-2018 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Since 5th August 2018, Vojnotehnicki Glasnik/Military Technical Courier has been a partner with Publons, the world’s leading peer review platform, part of Clarivate Analytics, which officially recognizes peer review contributions